Efektivitas Metode Total Physical Response (TPR) Terhadap Peningkatan Penguasaan Mufradat Siswa kelas IVB MI Al Huda Karangnongko - Hardiyanti, Iin; Rahman, M. Faqih Syifa (Mahira: Journal of Arabic Studies & Teaching, 2025)
Arabic language learning at MI Al Huda Karangnongko Yogyakarta has tended to be monotonous, as it is predominantly conducted through lecture, question-and-answer, and memorization methods, which has resulted in low student learning interest. This study aims to examine the effect of implementing the Total Physical Response (TPR) method on improving Arabic vocabulary mastery among fourth-grade students of class IV B at MI Al Huda. The research employed an experimental approach using a true experimental design, specifically the pretest–posttest control group design. The research sample consisted of two classes selected from the entire student population of MI Al Huda, with class IV B serving as the experimental group that received instruction using the TPR method, and class IV A serving as the control group that was taught using conventional instructional methods. Data analysis was conducted using a parametric statistical test in the form of an Independent Samples t-Test, assisted by SPSS version 25. The results of the analysis revealed a Sig. (2-tailed) value of 0.000, which is lower than the significance level of 0.05. Therefore, it can be concluded that the implementation of the Total Physical Response (TPR) method has a significant effect on the Arabic vocabulary mastery of fourth-grade students in class IV B at MI Al Huda Karangnongko Yogyakarta.